(Hesitant) Fuzzy sets on Sheffer stroke UP-algebras. Issue 5 (4th July 2022) - Oner, Tahsin; Katican, Tugce; Saeid, Arsham Borumand
Abstract: The aim of this study is to present (sup-hesitant) fuzzy SUP-subalgebras and fuzzy duplex SUP-sets on Sheffer stroke UP-algebra (in short, SUP-algebra). After defining (sup- hesitant) fuzzy SUP-subalgebras and fuzzy duplex SUP-sets of a SUP-algebra, we give their some properties and analyse whether the intersection or union of these subalgebras is a (sup-hesitant) fuzzy SUP-subalgebra of a SUP-algebra. It is shown that the level sets of (sup-hesitant) fuzzy SUP-subalgebras of a SUP-algebra are its SUP-subalgebras. Also, fuzzy duplex SUP-sets of a SUP-algebra are determined and studied the cases which these sets are SUP-algebras. Finally, the relationships between aforementioned structures are investigated.